A Review of the Novel Application and Potential Adverse Effects of Proton Pump Inhibitors - Yu, Li-Yuan; Sun, Lu-Ning; Zhang, Xue-Hui; Li, Yue-Qi; Yu, Lei; Yuan, Zi-Qing-Yun; Meng, Ling; Zhang, Hong-Wen; Wang, Yong-Qing (Advances in therapy, 2017)
Proton pump inhibitors (PPIs) are known as a class of pharmaceutical agents that target H + /K + -ATPase, which is located in gastric parietal cells. PPIs are widely used in the treatment of gastric acid-related diseases including peptic ulcer disease, erosive esophagitis and gastroesophageal reflux disease, and so on. These drugs present an excellent safety profile and have become one of the most commonly prescribed drugs in primary and specialty care. Except for gastric acid-related diseases, PPIs can also be used in the treatment of Helicobacter pylori infection, viral infections, respiratory system diseases, cancer and so on. Although PPIs are mainly used short term in patients with peptic ulcer disease, nowadays these drugs are increasingly used long term, and frequently for a lifetime, for instance in patients with typical or atypical symptoms of gastroesophageal reflux disease and in NSAID or aspirin users at risk of gastrotoxicity and related complications including hemorrhage, perforation and gastric outlet obstruction. Long-term use of PPIs may lead to potential adverse effects, such as osteoporotic fracture, renal damage, infection (pneumonia and clostridium difficile infection), rhabdomyolysis, nutritional deficiencies (vitamin B12, magnesium and iron), anemia and thrombocytopenia. In this article, we will review some novel uses of PPIs in other fields and summarize the underlying adverse reactions.